Bovine paratuberculosis, literature review (2021)
Bovine paratuberculosis (PTB) is a chronic disease caused by the bacillus Mycobacterium avium subspecies paratuberculosis (MAP). It is found worldwide and generates economic losses for producers due to the low productive performance of the animals and its long incubation period in which it is excreted through fecal matter without any clinical symptoms. It has been reported that the animals most susceptible to contracting the disease are calves. Diagnostic methods used for MAP include PCR, ELISA, fecal bacterial culture, MAP screening in tissue samples, and intradermal Johnina delayed skin hypersensitivity test. MAP is a bacterium with possible zoonotic potential due to its relationship with Crohn’s disease. Since there is no treatment for PTB, control mechanisms must be intensified in the production process.